Reshaping Curricula : Integrating Culturally Diverse/Mental Health Online Content to Prepare Work Ready Health Professionals : Final Report. - Muir-Cochrane, Eimear; Levett-Jones, Tracy; Rudd, Cobie; Barkway, Patricia; Edmondson, Wendy; McAllister, Margaret; Rigney, Daryle; O'Kane, Debra; Gillham, David; Wright, Victoria; Palmer, Christine (Office for Learning and Teaching, 2016)
Health professionals need to be able to assess mental health problems, as well as communicate effectively with people from different cultures. Over 27% of Australia's population is from migrant and refugee backgrounds with another 2.5% being Indigenous. One in five Australians will experience mental illness, with significant psychiatric morbidity for Indigenous Australian and culturally and linguistically diverse communities. As such, all health professionals will encounter these groups in providing care to them. Interprofessional education that integrates mental health and culture has been lacking in undergraduate health programs. This project addressed the priority area of Curriculum Design through the development, evaluation and dissemination of online guided learning journeys to prepare health science students in the interprofessional mental health assessment and management needs of specific cultural populations. Undergraduate students from nursing, psychology and health sciences will gain clinical and cultural mental health competence as they engage in simulated online interdisciplinary communication to provide culturally sensitive care.